Metacognitive self-regulation strategies on academic achievement among UNIMAS undergraduates - Kok,, Yan Jye. (Universiti Malaysia Sarawak, UNIMAS, 2010)
This paper investigates the relationship between metacognitive self - regulation strategies (MSR) and academic achievement among Unimas undergraduates. Specifically, this study examines the relationship between subcomponents of MSR and UNIMAS s tudents’ Cumulative Grade Point Average (CGPA). The five subcomponents of MSR are planning skills, information management strategies, monitoring, debugging strategies and evaluation. Academic achievement is measured based on the total average of overall ex amination scores (CGPA). Ninety students were randomly selected from Faculty of Cognitive Sciences and Human Development (FCSHD) in UNIMAS to take part in this research. Data was collected through a survey questionnaire which was adapted from Metacognive A wareness Inventory (MAI). The results showed that information management strategies, monitoring skill, and debugging strategies were significantly and positively correlated with academic achievement. Among the three significantly correlated pairs, debuggin g strategies have the highest degree of correlation with academic achievement. However, planning skill and evaluation skill subcomponents of MSR showed no significant relationship with academic achievement. It was also found that there was no programme - lev el difference between the data obtained from two sample groups in terms of the deployment of self - regulation strategies. The findings also showed that both CS and HRD students preferred to use information management strategies to develop their learning abi lity in order to achieve good results. This study concluded that metacognition self - regulation strategies are important to be developed among undergraduates to facilitate their learning process at the university.